Neuroinflammation associated with ultrasound-mediated permeabilization of the blood–brain barrier. Issue 6 (June 2022) - Jung, Olive; Thomas, Alec; Burks, Scott R.; Dustin, Michael L.; Frank, Joseph A.; Ferrer, Marc; Stride, Eleanor
Abstract : The blood–brain barrier (BBB) continues to represent one of the most significant challenges for successful drug-based treatments of neurological disease. Mechanical modulation of the BBB using focused ultrasound (FUS) and microbubbles (MBs) has shown considerable promise in enhancing the delivery of therapeutics to the brain, but questions remain regarding possible long-term effects of such forced disruption. This review examines the evidence for inflammation associated with ultrasound-induced BBB disruption and potential strategies for managing such inflammatory effects to improve both the efficacy and safety of therapeutic ultrasound in neurological applications. Highlights: The blood–brain barrier (BBB) plays both a physical and a physiological 'gatekeeping' role in maintaining brain homeostasis. In recent years, there has been increasing interest in understanding the role of the BBB in neurological disorders that were traditionally considered to be neuron-centric, for instance, Parkinson's disease (PD) and Alzheimer's disease (AD). Alternative drug delivery techniques such as focused ultrasound (FUS) are emerging as powerful tools to bypass the BBB and facilitate the treatment of neurological conditions. To enable widespread clinical use of these techniques, there is an urgent need to investigate and address the associated safety concerns, for example, the consequences of sterile inflammation that may be induced by BBB disruption.